Entrepreneuring for deprived urban communities: Exploring the role of micro‐entrepreneurship. Issue 3 (30th March 2021) - Colovic, Ana; Schruoffeneger, Marion
Abstract: This paper studies how micro‐entrepreneurs engage in entrepreneuring to generate social value for their communities. We study three cases of micro‐entrepreneurs operating in deprived urban communities in Brazil. Our findings reveal that micro‐entrepreneurs create social value by engaging in transformative, emancipatory, and connective entrepreneuring. We identify a three‐stage model of social value creation through entrepreneuring. We contribute to the literature by providing evidence of the emancipatory and transformative dimensions of entrepreneuring and extend understanding of this phenomenon to include the dimension of connectivity.